Making Care Better in the Context of Violence: The Limits of Blame - Swartz, Leslie (Violence against women, 2021)
This brief commentary is a response to the helpful responses to our article on the problem of the concept of gentle violence in obstetric care. We find ourselves in substantial agreement with our interlocutors. We suggest that naming individual actions on the part of health care personnel as violent may not be necessary for changing the behavior of these personnel and may in fact impede change. We suggest further that requiring health care personnel to accept our definitions of violence may in itself be an oppressive or epistemically violent act, probably less likely to lead to desired change than other approaches. We emphasize the need for more dialogue on victimology and the discursive complexities of trying to intervene in situations of structural violence.